Removability of exceptional sets for differentiable and Lipschitz functions - Craig, J.; Feinstein, Joel; Patrick, P. (American Mathematical Society, 2015)
We discuss removability problems concerning differentiability and pointwise Lipschitz conditions for functions of a real variable. We prove that, in each of the settings under consideration, a set is removable if and only if it has no perfect subsets.